Fenfluramine responder analyses and numbers needed to treat: Translating epilepsy trial data into clinical practice. (March 2021) - Sullivan, Joseph; Perry, M. Scott; Wheless, James W.; Galer, Bradley; Gammaitoni, Arnold
Abstract: Objective: Clinical trials typically report antiepileptic drug efficacy by evaluating reduction in monthly convulsive seizure frequency (MCSF) through group response (active versus placebo). Although useful for regulatory purposes, population statistics do not easily translate into clinical practice, where treatment decisions are made on an individual-patient basis. Responder analyses help bridge this gap by showing proportions of patients who achieved various MCSF improvement levels. Deriving numbers needed to treat (NNTs) to achieve clinically desirable response levels can further inform individual decision-making. We calculated the NNT with fenfluramine to achieve "clinically meaningful" (≥50%) or "profound" (≥75%) MCSF reductions in patients with Dravet syndrome (DS). Methods: NNT to achieve ≥50% or ≥75% MCSF reduction was assessed using longitudinal data from two phase 3 studies for adjunctive fenfluramine in DS patients aged 2–18 years. NNT was calculated: 1/((Experimental-Responder Rate)−(Control-Responder Rate)). Results: In Study 1, NNTs to achieve ≥50% and ≥75% MCSF reduction were 1.8 and 2.1 at 0.7 mg/kg/day fenfluramine. In Study 2, these NNTs were 2.0 and 3.1, respectively. These results were seen as early as Weeks 6–7 and were sustained through Weeks 14–15. Interpretation: For every two to three patients with DS treated with fenfluramine in these trials, one patient achieved ≥50% or ≥75% MCSF reduction, respectively, compared with placebo (large treatment effect size; Cohen's d≈0.8). Responder analyses and NNTs can aid in clinical decision-making by offering clinically important information that is complementary to the population mean data on the chance of an individual patient achieving meaningful levels of MCSF improvement. (NCT02682927/NCT02826863, NCT02926898) Highlights: Data from phase 3 clinical studies of fenfluramine in Dravet syndrome were used to: calculate NNTs to facilitate translating clinical trial data into clinical practice achieve NNT of 2–3 with fenfluramine for ≥75% reduction in seizures in DS calculate NNT of 8–20 for other AEDs for ≥50% fewer seizures in refractory epilepsy